Pre-hospital emergency care student experience with paediatric emergency cases in Johannesburg, Gauteng - Stein, Christopher Owen Alexander (My University, 2011)
Adequate exposure to paediatric pre-hospital emergency cases for students undertaking clinical learning is a key component of preparation for independent practise. Both clinical reasoning and psychomotor skills require practise in a realistic environment in order to best equip the qualifying practitioner for demands of the real world of pre-hospital emergency care. The aim of this study was to retrospectively describe the exposure of pre-hospital emergency care students in the University of Johannesburg‟s National Diploma in Emergency Medical Care programme to emergencies involving paediatric patients in the Greater Johannesburg Metropolitan area over a continuous eight year period, between 1 January 2001 and 31 December 2008. Patient care records contained in an electronic clinical learning management information system entered over the eight-year study period were analysed in order to characterise the exposure of students to paediatric emergency cases in general, and clinical skills performed during this exposure. Results showed that, with the exception of infants and children seen by first year students, median exposure to paediatric emergency cases for students in all academic years was below 50%. Exposure to emergencies involving younger patients was generally lower than that for older patients, however the acuity of patients increased with decreasing age. Exposure to most clinical skills also decreased with decreasing patient age. Opportunities for students to practise critical or invasive skills were relatively rare. Suggestions for the improvement of student exposure to paediatric emergency cases and clinical skills include a period of internship and greater utilisation of hospital-based clinical skills exposure and practice.
MSc (Med) Emergency Medicine, Faculty of Health Sciences, University of the Witwatersrand
Keywords: emergency care; children; paediatric emergencies; pre-hospitalisation